Intestinal Obstruction due to Ileal Duplication Cyst and Malrotation in a Preterm Neonate - Laxman Basany; Roja Aepala; Madhu Mohan Reddy Bellary; Maruthi Chitneni (EL-Med-Pub, 2015)
Please see fulltext